Evaluating a picture archiving and communications system workstation - Erickson, Bradley J. (Springer-Verlag, 1999)
An efficient environment for picture archiving and communications systems (PACS) in the radiology department and throughout a medical practice requires good hardware, good software, and integration of the information sources that exist in a radiology department and institution. This tutorial will describe some of the considerations in evaluating a PACS workstation, with a view to the hardware requirements, user interface designs and integration with the information systems.